Kevalidan dan Kepraktisan LKPD Berbasis PBL terhadap Kemampuan Penalaran Matematis pada Materi Relasi dan Fungsi - Febriyanti, Quratul Aini; Fitrianti, Yuli; Ramury, Feli (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
The development of student-based worksheets Problem-Based Learning (PBL) was an alternative to overcome the lack of mathematical reasoning skills in the subject of Relations and Functions. This study aims to produce worksheets based on PBL on relations and functions that are valid and practical for mathematical reasoning abilities. The type of research used was a development study using the development flow preliminary research and prototyping stage (formative evaluation Tessmer groove). The subjects of this study were students of class VIII SMP Negeri 19 Palembang. The data collection techniques used were walkthroughs in the form of an expert questionnaire, student questionnaires, interviews, and documentation. Data validation student worksheets obtained with 3 validators and practicality data obtained from practicality questionnaires given to students. The results showed the validity based on 3 validators who said it was valid and feasible to use, the practicality percentage was 82.33% in the very practical category with an average percentage of students' mathematical reasoning abilities of 83% in the very practical category. So it would be concluded that PBL-based student worksheets on the material of relations and functions tested are valid and practical for mathematical reasoning abilities.